Dynamic postural stability changes of the subjects with toe-in gait due to increase in femoral head anteversion angle during walking - Mohammad Taghi Karimi; Mahmood Bahramizadeh; Amirhossein Zare; Hanieh Khaliliyan; Alireza Khaghani; Shahla Mohajeri; Majid Ansari; Farhad Ghaffari; Arash Sharafatvaziri (Advances in Medicine, Psychology, and Public Health)
Background: Toe-in gait may be caused by an increase in femoral head anteversion angle. The objective of this study was to assess the impact of toe-in gait on stability during walking. Method: Two groups were recruited for the study: normal subjects and those with toe-in gait (resulting from an increase in femoral head anteversion angle). Spatiotemporal gait parameters and center of mass (COM) motion were used to evaluate dynamic postural stability. Results: The mean stride length for normal subjects was 1.1±0.141 meters, compared to 0.943±0.185 meters for those with toe-in gait (p-value=0.01). There was no significant difference in walking speed between the two groups (p-value= 0.3). The motion of the COM in the vertical (p-value= 0.02) and mediolateral (p-value= 0.01) directions was significantly less in the toe-in gait group compared to normal subjects. Conclusion: The findings of this study suggest that individuals with toe-in gait exhibit greater stability while walking compared to normal subjects.